Odpowiedź:
Szczegółowe wyjaśnienie:
a) [tex]\frac{1}{3}x-2=x+2[/tex] /*3
[tex]x-6=3x+6\\x-3x=6+6\\-2x=12\\x=-6[/tex]
b) [tex]1-\frac{6}{7}x=\frac{4}{7}[/tex] /*7
[tex]7-6x=4\\-6x=4-7\\6x=3\\x=\frac{1}{2}[/tex]
c) [tex]6(\frac{1}{4} x-2)=18[/tex] /:6
[tex]\frac{1}{4} x-2=3[/tex] /*4
[tex]x-8=12\\x=12+8\\x=20[/tex]
d) [tex]\frac{x}{6}-\frac{1}{6} =1[/tex] /*6
[tex]x-1=6\\x=6+1\\x=7[/tex]
e) [tex]-2(2x-1)=\frac{x}{3}[/tex]
[tex]-4+x=\frac{x}{3}[/tex] /*3
[tex]-12x+6=x\\-12x-x=-6\\13x=6\\x=\frac{6}{13}[/tex]
f) [tex]\frac{2}{5}(3-x)=-2[/tex] /*[tex]\frac{5}{2}[/tex]
[tex]3-x=5\\-x=5-3\\x=-2[/tex]
g) [tex]\frac{3}{4}( 2-3x)=-6[/tex] /*[tex]\frac{4}{3}[/tex]
[tex]2-3x=-8\\-3x=-8-2\\3x=10\\x=\frac{10}{3}=3\frac{1}{3}[/tex]
h) [tex]\\\frac{1}{5}(x-3)=9-x[/tex] /*5
[tex]x-3=45-5x\\x+5x=45+3\\6x=48\\x=8[/tex]
i) [tex]\frac{0,6+x}{2}=x+1[/tex] /*2
[tex]0,6+x=2x+2\\x-2x=2-0,6\\-x=1,4\\x=-1,4[/tex]